Frequency of Difficult Cholecystectomy in Patients with Thick Walled Gall Bladder - Junaid Zaman; Rahila Razzak; Syed Imaduddin (ziauddin University, 2024)
Background: Laparoscopic cholecystectomy is the procedure of choice for cholecystitis. There are variable rates of conversion of laparoscopic cholecystectomy to open cholecystectomy. Various studies have highlighted gall bladder wall thickness and age as independent risk factors for conversion from laparoscopic to open procedure. This study was done to determine the frequency of conversion of laparoscopic cholecystectomy to open cholecystectomy in patients undergoing laparoscopic cholecystectomy with a gall bladder wall thickness of more than 3mm as determined on pre operative ultrasound. Objective: To find frequency of conversion to open procedure in patients undergoing laparoscopic cholecystectomy with a gall bladder wall thickness of more than 3mm as determined on pre operative Ultrasound. Methods: This Case series was conducted at the Surgical Unit IV Civil Hospital Karachi, Pakistan from 15th July 2012 to 15th January 2013. A total of 129 patients were included in the study with gall bladder wall thickness of more than 3mm on Ultrasound. Patients were stratified according to age, sex, gall bladder wall thickness, frequency of difficult cholecystectomy and duration of disease. Results: A total of 129 patients were included in the study. Female to male ratio is 5.7:1. The mean age of patients was 43.33±11.5 years. The average gall bladder wall thickness was 4.07±0.63 mm and duration of disease was 4.53±4.67 years. Regarding preoperative findings, bleeding during separation from liver bed was the commonest finding in general i.e. 35.7% followed by local adhesions 33.3% and perforation of gall bladder was observed in 7.8% cases. All (n=13) patients who had conversion to an open procedure had wall thickness between 4.1 to 6 mm. Similarly rate of conversion was found to be in higher in patients with symptoms for more than 5 years (i.e. 9 out of 24). Conclusion: Ultrasound for gall bladder wall thickness is a good predictor for difficult cholecystectomy. It should be used as anticipative measure for difficult cases and patient should be properly counseled regarding chances of conversion. Key Words: Difficult Laparoscopic Cholecystectomy, Gall Bladder Wall Thickness, Conversion To Open Cholecystectomy.